Asymmetric impact of oil price on inflation in Nigeria - Sani Bawa; Ismaila S. Abdullahi; Danlami Tukur; Sani I. Barda; Yusuf J. Adams (CBN Journal of Applied Statistics, 2020)
This study examines the impact of oil price shocks on inflation in Nigeria. A Non-Linear Autoregressive Distributed Lag (NARDL) approach was applied on quarterlydata spanning 1999Q1 to 2018Q4. Results showed that oil price increases led toincrease in headline, core and food measures of inflation in Nigeria. However, a de-cline in oil price resulted in a decline in the marginal cost of production and culmi-nated in moderation of domestic inflation. Furthermore, negative oil price shocks ledto higher inflation in Nigeria when exchange rate is dropped from the models, indi-cating that exchange rate absorbed the impact of oil price declines earlier, as loweroil prices culminated in lower external reserve, depreciation of the naira and ulti-mately higher inflationary pressures. Also, core inflation tends to respond more to oilprice increases than food inflation. These results were robust to changes in economet-ric specifications and sample period. The study recommends that monetary policy ac-tions of the Central Bank of Nigeria should focus on taming core inflation in periodsof substantial oil price increases while strengthening its efforts at ensuring domesticsustainability in food production through its agricultural intervention programmesto further minimize the impact of international oil prices on food inflation. Similarly,the fiscal authorities should ensure that the fiscal stance is not excessively procyclicalin periods of rising oil prices .
Keywords: E31; Q43; 330; Asymmetry; inflation; nonlinear autoregressive distributed lag; oil price shocks